Improved In Vitro Antimycobacterial Activity of Trinuclear Complexes Cobalt(II, III) and Iron(III) with 2‐Furoic Acid against Mycolicibacterium smegmatis. Issue 38 (9th October 2020) - Lutsenko, Irina A.; Yambulatov, Dmitriy S.; Kiskin, Mikhail A.; Nelyubina, Yulia V.; Primakov, Petr V.; Bekker, Olga B.; Levitskiy, Oleg A.; Magdesieva, Tatiana V.; Imshennik, Vladimir K.; Maksimov, Yurii V.; Sidorov, Aleksey A.; Danilenko, Valery N.; et al.
Abstract: The reaction of cobalt(II) and iron(III) pivalates with anions of 2‐furancarboxylic acid (pyromucic acid, Hfur) yielded trinuclear homometallic complexes with linear ([Co3 (fur)6 (phen)2 ] (1, phen=1, 10‐phenanthroline)) and triangular ([Co3 O(fur)6 (H2 O)3 ] (3 ), [Fe3 O(fur)6 (THF)3 ] ⋅ 3THF (4 )) structures of the metal moiety. The hexanuclear mixed carboxylate cobalt complex [Co6 (piv)8 (Hpiv)4 (fur)2 (OH)2 ] (2, piv − =(CH3 )3 COO − ) was isolated as an intermediate in the synthesis of 3 . According to CVA data, complex 3 contains bivalent and trivalent cobalt ions. According to Mossbauer spectroscopy data, all the iron(III) atoms in 4, which is an isostructural analogue of 3, are solely in the high‐spin state. The antibacterial activity of compounds 1 –4, K(fur) (5 ) and Na(fur) (6 ) was determined in vitro against a non‐pathogenic Mycolicibacterium smegmatis strain. The results of in vitro biological tests against Mycolicibacterium smegmatis showed a high bioactivity of complexes 1 and 4 . Abstract : Using alternative experimental conditions (inert and air atmospheres, a number of homometallic furoate complexes were obtained: a compound with linear structure [Co II 3 (fur)6 (phen)2 ], an oxo‐centered complexes triangular structure [Co III 2 Co II O(fur)6 (H2 O)3 ], [Fe3 O(fur)6 (THF)3 ] and hexanuclear complex [Co II 6 (piv)8 (Hpiv)4 (fur)2 (OH)2 ] (3 ). All obtained complexes exhibit biological activity in vitro against Mycolicibacterium smegmatis .